Performance Improvement in Combating Poverty (International Conference of Graduate School on Sustainability (ICGSS), 2021)
The problem of poverty in the Special Region of Yogyakarta of Indonesia, has not shown a decline. In this regard, this study aims to analyze the effect of the effectiveness of poverty alleviation planning, reporting, controlling, and the smart cities on the performance of regional administrators for poverty alleviation. The number of samples were 270 respondents. The quantitative method as well as structural equation modeling (SEM), is used. The poverty alleviation planning, reporting, and controlling have significant effect on the effectiveness of smart cities, on the performance of the local government, and smart cities as moderating variable.